Pengaruh Brand Image, Promosi, Kualitas Produk, Harga, Dan Lokasi Terhadap Keputusan Pembelian Teh Poci Paranadipa Jember - Yulia Tri Wulandari; Dimyati; Karim Budiono (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to determine and analyze the influence of brand image, promotion, product quality, price and location on purchasing decisions at Teh Poci Paranadipa Jember. The research method used is quantitative descriptive with data collection techniques through questionnaires to 60 respondents selected using the purposive sampling method. In this data, data was collected by observation, interviews, literature studies and questionnaires. The analysis used includes data instrument testing (validity testing and reliability testing), multiple linear regression analysis, classical assumption testing (normality testing, multicollinearity testing, heteroscedasticity testing), and hypothesis testing (F test, t test, and coefficient of determination testing). Based on the results of the analysis, this study shows that the F test of brand image, promotion, product quality, price and location variables simultaneously influence purchasing decisions. While the results of the t test in this study indicate that the product quality variable has a positive and significant effect on purchasing decisions, while brand image, promotion, price and location do not have a significant effect on purchasing decisions.